Pola Resistensi Bakteri Penyebab Infeksi Saluran Kemih (ISK) Terhadap Antibakteri di Pekanbaru - Endriani, Rita; Andrini, Fauzia; Alfina, Dona (Jurnal Natur Indonesia, 2010)
Urinary Tract Infection (UTI) is caused by a variety of microorganism, but bacteries are more often. Antibacterial isthe empiric treatment for UTI. The antibacterial resistance pattern of UTI can be changed by the place and time.Urine culture test and sensitivity test will help us to choose the effective treatment. The purpose of this researchis to find out the pattern of UTI in Pekanbaru. Results of this research showed that UTI bacterial resistancy mostlyfound in Gram negative bacateria with penicillin and 1 st cephalosporin antibiotic.